Renal artery aneurysm repair by auto-transplantation in a 4-year-old girl with renovascular hypertension - Sergio Assia-Zamora; Nicos Kessaris; Colin Forman (Elsevier, 2021)
Introduction: Hypertension is an uncommon but potentially serious finding in children. Renovascular disease is responsible for 8-10% of all cases and is treatable. Case presentation: We present a 4 year old girl with hypertension of 120-148 mmHg as an incidental finding while having yearly follow up due to a dermatofibroma on her back. She was otherwise well with no other significant medical issues. She received treatment with antihypertensives and multiple laboratory and imaging studies were performed; the imaging studies demonstrated a fusiform aneurysm of the left renal artery. After reviewing the images, and following discussion in a multidisciplinary team including transplant and vascular surgeons, interventional radiologists, paediatric nephrologists and a hypertension nurse specialist, a decision was taken to repair the aneurysm by performing a kidney auto-transplant. The child underwent successful surgery and on follow up she is normotensive without medications and has normal renal function. Discussion: Although the technique of treating renal artery aneurysm by extracorporeal repair and auto-transplant has been described in adults, in paediatrics this is still an innovative technique. This is the first successful report of a RAA repair in the paediatric population. Conclusion: This is the first descriptive case report of a successful aneurysm resection and renal auto-transplant in a child.